BABANDINGAN NOVÉL LAIN ÉTA KARYA MOH. AMBRI JEUNG DJEUMPA ATJEH KARYA H.M. ZAINUDDIN: Ulikan Struktural Jeung Étnopédagogik - Witri Gustiani, - (2018)
The aims of this research is to describe about the structure comparison between the novel Lain Eta by Moh. Ambri and Djeumpa Atjeh by H.M. Zainuddin, and the analysis of ethnopedagogical values. These two novels have the same theme, named kawin paksa.The theology used in this research is comparison between literature region by Endraswara, the facts if story by Robert Stanton, and also etnhnopedagogy values by Sudaryat. The method in this research is description, and literature review. These two novels have the same main characters, there is the girl who can't marriage with their loves because the parents is not agree. Their parents wants to have a son-in-law by the men which parents choose, and the conflict was stared from this. This research hopes is can be add insight about comparative literature, and comparative literature region in Indonesia.